SYUKUR DAN PUJIAN MENURUT MUHAMMAD SHALEH DARAT AL-SAMARANI: KAJIAN ATAS (QS. Al-FĀTIHAH [1]: 2) TAFSĪR FAIDH AL-RAHMĀN - Egi Sukma Baihaki (Tanzil: Jurnal Studi Al-Quran, 2016)
Praise and gratitude (syukr) are closely related to forms of worshiping of a servant to his Lord. Many verses of the Qur’an show this as it is associated with favors that God has bestowed upon His creation. However, there are still many people who neglect and forget to thank and praise God for all the blessings that God has given to them. Either because of their own humiliation, as well as the weakness of those who are unable to understand the nature of gratitude and praise itself. This article will see how this message appears in (QS. al-Fātiẖah [1]: 2) where Allah orders his worshipers to thank and praise him, while God Himself Who started praising Him. Therefore, the aim of this paper is to introduce how such views and ideas appear through Muhammad Sholeh Darat al-Samarani, mainly when interpreting (QS. al-Fātiẖah [1]: 2) in his book, Tafsīr Faidh al-Raẖmān.